DEHBA (di-2-ethylhexylbutyramide) gamma radiolysis under spent nuclear fuel solvent extraction process conditions. (May 2020) - Horne, Gregory P.; Mezyk, Stephen P.; Mincher, Bruce J.; Zarzana, Christopher A.; Rae, Cathy; Tillotson, Richard D.; Schmitt, Nicholas C.; Ball, Richard D.; Ceder, Joakim; Charbonnel, Marie-Christine; Guilbaud, Philippe; Saint-Louis, George; et al.
Abstract: Di-2-ethylhexylbutyramide (DEHBA) has been proposed as part of a hydro-reprocessing solvent extraction system for the co-extraction of uranium and plutonium from spent nuclear fuel. However, there remains a lack of quantitative understanding of the impact of chemical environment on the radiation chemistry of DEHBA, especially under conditions expected in real-world solvent extraction processes. Therefore, we have undertaken a systematic investigation into the radiolytic degradation of DEHBA in n -dodecane under fully aerated and biphasic conditions. DEHBA integrity and degradation product formation were measured for both extraction (in contact with 4.0 M HNO3(aq) ) and stripping (in contact with 0.1 M HNO3(aq) ) formulations. At the lower acidity the rate of DEHBA/ n -dodecane degradation was slow ( G  = −0.26 ± 0.02 μM J −1 ) whereas at the higher acidity this degradation was about 35% faster ( G  = −0.35 ± 0.02 μM J −1 ). Both values were much less than analogous measurements under deaerated conditions. Under continuously aerated conditions, FTIR and ESI-MS measurements identified the two major degradation products, bis- 2-ethylhexylamine (b2EHA) and N -(2-ethylhexyl)butyramide (MEHBA), as well as the presence of additional oxidized product species. Solvent system performance was also investigated using uranium extraction and strip distribution ratio measurements. These studies showed that there was only minimal change in uranium extraction and stripping performance with absorbed gamma dose. Highlights: Radiolytic degradation of DEHBA in n -dodecane for real-world solvent extraction processes. Lower degradation rates of ligands under continuously sparged conditions. FTIR and ESI-MS measurements of radiation-induced degradation products. Minimal changes in uranium extraction and stripping performance with absorbed gamma dose.